Happy Despite Pain: A Randomized Controlled Trial of an 8-Week Internet-delivered Positive Psychology Intervention for Enhancing Well-being in Patients With Chronic Pain. Issue 11 (November 2017) - Peters, Madelon L.; Smeets, Elke; Feijge, Marion; van Breukelen, Gerard; Andersson, Gerhard; Buhrman, Monica; Linton, Steven J.
Abstract : Objectives: There is preliminary evidence for the efficacy of positive psychology interventions for pain management. The current study examined the effects of an internet-based positive psychology self-help program for patients with chronic musculoskeletal pain and compared it with an internet-based cognitive-behavioral program. Materials and Methods: A randomized controlled trial was carried out with 3 conditions: an internet-delivered positive psychology program, an internet-delivered cognitive-behavioral program and waitlist control. A total of 276 patients were randomized to 1 of the 3 conditions and posttreatment data were obtained from 206 patients. Primary outcomes were happiness, depression, and physical impairments at posttreatment and at 6-month follow-up. Intention-to-treat analyses were carried out using mixed regression analyses. Results: Both treatments led to significant increases in happiness and decreases in depression. Physical impairments did not significantly decrease compared with waitlist. Improvements in happiness and depression were maintained until 6-month follow-up. There were no overall differences in the efficacy of the 2 active interventions but effects seemed to be moderated by education. Patients with a higher level of education profited slightly more from the positive psychology intervention than from the cognitive-behavioral program. Discussion: The results suggest that an internet-based positive psychology and cognitive-behavioral self-help interventions for the management of chronic pain are clinically useful. Because the self-help exercises as used in the current program do not require therapist involvement, dissemination potential is large. Further studies should examine whether it can best be used as stand-alone or add-on treatment combined with established pain treatment programs. Abstract : Supplemental Digital Content is available in the text.